The influences of hygiene attributes toward customers fear of covid-19 at thai restaurant in kota bharu, Kelantan - Nur A’ina Sofia Sufhian; Nur A’watief Mohd Nawi; Nur Afeeqa Ilani Norazuki (2023)
In Malaysia, the impact of COVID-19 had put management in the business industry under pressure. The prolonged spread of the coronavirus had caused business in Malaysia to not grow. This study combined the characteristics of restaurant hygiene such as hygiene of customer-use, personal hygiene of staff and hygiene of workspaces. The purpose of this study was because not many studies had been conducted to investigate the perception of risk in doing business following the health crisis and consumer fear of the virus. Therefore, this study was designed to examine the influence of cleanliness on customers' fear of COVID-19 on businesses in Malaysia. This study would use a questionnaire as a method to collect data and it would be analyzed using SPSS. This study was believed to give good insight to academics and practitioners in preparing them for the post-corona field for the new normal after the limited life experience during the unprecedented epidemic. Keyword : Fear of COVID-19